Rekayasa Sistem Informasi Manajemen Perakitan Berbasis Group Technology untuk Mendukung Proses Assembly Frame Body Bus - Murdiyanto, Danang; Pratikto, Pratikto; Santoso, Purnomo Budi (Jurnal Rekayasa Mesin, 2016)
PT. APW is a manufacturing company of the bus body. One of the production process department in PT. APW is frame work department. It is in charge of making the bus body frame. The problem faced in this department is inadequationvof the current system. It is because the work is done manually and is not by using computer applications with database systems. The study used the assembly information management system based on Group Technology to help its assignment of bus body frame assembling process and the work report. Management Information System Design Assembly (SIMPER) were performed by using the Microsoft Access 2013 to produce a prototype application SIMPER consisting of phase identification, analyzing, planning, designing, implementating and testing. By designing this SIMPER prototype application, it is expected to meet the needs of users of information systems in Production Manager, SPV and Admin employees.